Development of Flipbook Electronic Teaching Materials for Implementing the Scientific Approach in Indonesian Language Learning for Vocational High School Students - Yeni Sulaeman; Ade Hikmat; Wini Tarmini (AL-ISHLAH: Jurnal Pendidikan, 2025)
The rapid advancement of information technology has significantly transformed educational practices, particularly in the shift from conventional to digital learning models. In response to this transformation and the implementation of online learning policies by the Ministry of Education and Culture, this study aims to develop electronic teaching materials using a scientific approach for Indonesian language instruction in Class XI of vocational high schools. This research employed a development research design using the 4D model by Thiagarajan, which includes the stages of Define, Design, Develop, and Disseminate. However, the study focused solely on the first three stages due to time and resource constraints. The teaching materials were developed in the form of flipbook-based electronic modules and subjected to expert validation. Three domains were assessed: content (by material experts), language (by linguists), and visual design (by graphic experts). The validation results showed that the electronic flipbook teaching materials achieved an average feasibility score of 83.32%, which falls into the "Very Appropriate" category. Feedback from experts indicated strong alignment with curriculum standards, appropriate language usage for the target audience, and effective visual presentation. In conclusion, the developed flipbook-based electronic teaching materials are highly suitable for use in Class XI Indonesian language instruction, particularly in online learning contexts. Future research should focus on the dissemination stage and include empirical testing of learning outcomes with students to determine effectiveness in real classroom settings.